2023
DOI: 10.1126/science.abq1218
|View full text |Cite
|
Sign up to set email alerts
|

Has China’s Young Thousand Talents program been successful in recruiting and nurturing top-caliber scientists?

Abstract: In this study, we examined China’s Young Thousand Talents (YTT) program and evaluated its effectiveness in recruiting elite expatriate scientists and in nurturing the returnee scientists’ productivity. We find that YTT scientists are generally of high caliber in research but, as a group, fall below the top category in pre-return productivity. We further find that YTT scientists are associated with a post-return publication gain across journal-quality tiers. However, this gain mainly takes place in last-authore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 43 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In terms of the total number of science and technology publications in scientific journals, China has now surpassed the United States as the world leader ( 13 ). Four explanations accounting for China’s recent success in science and technology development are 1) a large population and human capital base, 2) a labor market rewarding academic meritocracy, 3) a centralized government willing to invest in science, and 4) the return migration of foreign-trained scientists and engineers of Chinese descent to China ( 5 , 14 ). Scientists of Chinese descent living and working overseas have been recruited to China by a combination of factors: large and fast-growing investments in science, high social prestige and attractive financial rewards tied to positions in Chinese institutions, and capable research collaborators and assistants.…”
Section: The Reverse Brain Drainmentioning
confidence: 99%
“…In terms of the total number of science and technology publications in scientific journals, China has now surpassed the United States as the world leader ( 13 ). Four explanations accounting for China’s recent success in science and technology development are 1) a large population and human capital base, 2) a labor market rewarding academic meritocracy, 3) a centralized government willing to invest in science, and 4) the return migration of foreign-trained scientists and engineers of Chinese descent to China ( 5 , 14 ). Scientists of Chinese descent living and working overseas have been recruited to China by a combination of factors: large and fast-growing investments in science, high social prestige and attractive financial rewards tied to positions in Chinese institutions, and capable research collaborators and assistants.…”
Section: The Reverse Brain Drainmentioning
confidence: 99%
“…In recent decades, there have been increasing discussions about talents, impact, employment, and mobility, including the statistical modeling of mobility patterns, career development, and policy implications (Cao et al, 2020;Clauset et al, 2015;Deville et al, 2014;Netz et al, 2020;Petersen, 2018;Vásárhelyi et al, 2021;Way et al, 2017;Zhang et al, 2019;Zweig et al, 2020), etc. Shi et al found out that the Young Thousand Talents Program in China (talent with cross-border movement) is successful in attracting high academic caliber but not the top ones compared to those who get the talent hats without returning to China (Shi et al, 2023), Zhao and Cao et al found that the returnees with cross-border mobility did not show advantages on scientific productivity (Zhao et al, 2023) but were more likely to publish higher impact works and…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the matching designs have been used in observational data to reduce the confounding influence in science of science and bibliometrics, including topics in gender disparities, citation prediction, mobility, prizewinning, team performance, field growth, collaborations, etc. (Azoulay et al, 2017;Huang et al, 2023;Jin et al, 2021;Reschke et al, 2018;Shi et al, 2023;Zhu et al, 2023) and the development of network tools to studies scientific careers and science (Fortunato et al, 2018;Wang et al, 2013;Way et al, 2019;Zeng et al, 2017). In general, the matching techniques are used to find observational "twins" before the treatment and estimate the treatment effects by comparing the posterior difference between them.…”
Section: Introductionmentioning
confidence: 99%